Aldo Palazzeschi's Works: Works between Literature and Art - Mohammad Hossein Ramadan Kiaei; Zohreh Montasseri (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Aldo Palazzeschi, with the pen name of Aldo Giurlani, is a celebrated 20th-century Italian poet and novelist. In the early years of the twentieth century, Palazzeschi, following some of the Western theories of thought such as that of Nietzsche's, has created unique works in modern Italian literature, and that is why his poems and novels have significant innovations. Undoubtedly, the author's early literary activities were influenced by his close relationships with artists, especially painters of his time. The traces of theater art can also be clearly seen in the works of the author's youth years. The present study attempts to study the literary works of Aldo Palazzeschi from the viewpoint of contemporary Italian literary critics such as Sanguinetti, Ungaretti, etc., and also attempts to examine the influence of Crepuscolarismo principles on Palazzeschi's attitudes and works of his youth years on the one hand, as well as, to study the influence of Futurism's theories on his other works, on the other hand.